Hydrolysis and solubilization of corn gluten by Neutrase - Apar, Dilek Kilic; Ozbek, Belma (WILEY, 2007)
Hydrolysis and solubilization of corn gluten were performed using a commercial protease preparation Neutrase. The effects of substrate concentration, enzyme concentration, temperature, pH and hydrolysate amount on the degree of hydrolysis and solubility of corn gluten were investigated depending on processing time. Trials were conducted in a batch reactor and degrees of hydrolysis were computed using a pH-stat method. Results show that solubility and degree of hydrolysis were almost linearly related in all process conditions applied except in the case of hydrolysate addition. Optimum conditions for hydrolysis and solubilization were obtained as 10 g L-1 protein concentration, 4mL L-1 enzyme concentration, 45 degrees C and pH 6.5. The mechanism of the kinetics was explained by taking into consideration association binding between the enzyme and substrate. The kinetics of hydrolysis and solubilization for all experiments performed were represented by exponential association equations that have not been used in the literature before. Also, to illustrate the effect of process variables on hydrolysis and solubilization, some modelling studies were performed. (c) 2007 Society of Chemical Industry.
Keywords: corn gluten; Neutrase; hydrolysis; solubilization; kinetics; modelling; ENZYMATIC-HYDROLYSIS; FUNCTIONAL-PROPERTIES; KINETIC-MODEL; WHEY PROTEINS; INACTIVATION; MECHANISM; Biotechnology & Applied Microbiology; Chemistry; Engineering